Foreign Language Speaking Anxiety: A Study of English Language Learning - Silvia Rahmadani; Fauzul Etfita (Indonesian Journal Of Educational Research and Review, 2022)
Speaking is the act of conveying information or expressing ideas and feelings in spoken English. Anxiety becomes a barrier to language mastery. This study analyse students' speaking anxiety in English. This research used quantitative research methods. Researchers selected class B of third semester consisting of 40 English Language Education students taken with purpossive sampling. Research instrument are used to obtain data from questionnaire. Meanwhile, the data collected by using Google Form. The total number of questions consists of 18 statements using the Likert Scale. According to the results of the questionnaire, the students have anxiety about speaking English, as evidenced by the percentage of responses in the question, which indicated that students had anxiety about speaking English at the time of wanting to speak while the teaching and learning process was in progress. Researchers discovered numerous findings from the anxiety of speaking English after analyzing the data. First, researchers discovered that the following cause contribute to anxiety in English-speaking students: fear self-prediction, irrational faith, sensitivity to dangers, sensitivity to anxiety, attribution of incorrect body signals, and inadequate self-efficacy. Second, the causes of students' speech anxiety are that students are not confident to speaking English, are afraid to make mistakes when speaking, anxious when teachers are asked to speaking, and embarrassed to perform in front of the class.